2013
DOI: 10.1371/journal.pone.0064261
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Allogenenic Blood Transfusion Is Associated with Worse Clinical Outcomes for Hepatocellular Carcinoma: A Meta-Analysis

Abstract: Background and ObjectiveThe impact of perioperative allogenenic blood transfusion (ABT) on clinical outcomes for hepatocellular carcinoma (HCC) is conflicting and unclear. The aim of this meta-analysis is to evaluate the association between ABT and HCC clinical outcomes. Outcomes evaluated were all-cause death, tumor recurrence and postoperative complications.MethodsRelevant articles were identified through MEDLINE search (up to November 2012). Meta-analyses were performed by using the fixed or random effect m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
92
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 48 publications
(72 reference statements)
10
92
0
2
Order By: Relevance
“…Recent studies had demonstrated that peri-operative allogeneic blood transfusion had an adverse effect on patients with surgical intervention in various malignancies (Liu et al, 2013;Meng et al, 2013;Ramos et al, 2003;Sugita et al, 2008;Wang et al, 2015). Some of these investigations further indicated that peri-operative transfusion of RBC product, rather than post-operative, was highly associated with prolonged hospital stay as well as increased morbidity and mortality (Ramos et al, 2003;Sugita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies had demonstrated that peri-operative allogeneic blood transfusion had an adverse effect on patients with surgical intervention in various malignancies (Liu et al, 2013;Meng et al, 2013;Ramos et al, 2003;Sugita et al, 2008;Wang et al, 2015). Some of these investigations further indicated that peri-operative transfusion of RBC product, rather than post-operative, was highly associated with prolonged hospital stay as well as increased morbidity and mortality (Ramos et al, 2003;Sugita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis performed by Liu et al [11] demonstrated that allogeneic blood transfusion (ABT) was associated with adverse clinical outcomes for hepatocellular carcinoma patients undergoing surgery, including increased death, recurrence and complications. PBT in patients with bladder cancer was associated with increased morbidity and mortality after RC in several observational studies [12, 13], but other studies [14, 15] did not show this association in multivariable analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Reported risk factors for blood transfusion include preoperative anemia (hemoglobin level < 125 g/L), extrahepatic procedure, caval exposure, major hepatectomy, tumour diameter, thrombopenia, cirrhosis and repeat liver resection. 4,6,7 It has been shown that perioperative allogeneic blood transfusion is a risk factor for complications and death 2,3,8,9 and may reduce disease-free survival after resection of hepatocellular carcinoma 10 and colorectal liver metastases. 11,12 Consequently, a reduction of the allogeneic blood transfusion rate would be welcome.…”
Section: Discussionmentioning
confidence: 99%